The Influence of Self-Regulated Learning Model In Basketball Games on Learning Motivation of SMP Negeri 1 Telagasari Students - Wijaya, Karta; Oktavia, Rizka; Abdillah, Yusha Nura; Suseno, Ihsan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Learning is a very strategic effort to achieve the expected goals. One of the delivery of creative and innovative teaching is by modifying a lesson to make it more interesting and to make students enthusiastic in participating in physical education, sports and health lessons. The problem that currently arises is that students are less comfortable when faced with standard tools such as basketball. Students complained because the ball used felt heavy when doing shooting techniques. So that modification techniques are needed in this game. The purpose of this study was to determine the influence of self-regulated learning models using modified basketballs on the learning motivation of class XI students of SMPN 1 Telagasari. This study used the Pretest-Posttest research design, with a population of class XI students of SMPN 1 Telagasari totaling 440 students and using a sample of class XI students of SMPN 1 Telagasari totaling 29 which were taken by using the normality test technique, homogeneity, and paired sample test. Based on the results of the research that has been done, the researcher can conclude that the results of this study are good and have an effect on students' learning motivation by using modified basketball.